PENGARUH METODE SOLMISASI PADA LAGU “BURUNG KAKAK TUA” MELALUI MEDIA ANGKLUNG TERHADAP KEMAMPUAN DAYA INGAT ANAK USIA 5-6 TAHUN: Penelitian Eksperimen pada Anak Usia Dini - Irma Sholikhah; Nurhenti Dorlina Simatupang; Sri Widayati; Yes Matheos Lasarus Malaikosa (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
Memory ability is an important aspect in the cognitive development of early childhood because it plays a role in the process of storing, processing, and recalling information received. However, the results of initial observations at DWP Jono Kindergarten showed that some children in group B still had difficulty remembering the sequence of notes, song lyrics, and the sound of the angklung during singing activities. The angklung musical instrument available at school has not been utilized as a learning tool, so children have not gained musical experience that can support memory strengthening. This study aims to analyze the effect of the solmization method on the song